PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP PRESTASI BELAJAR IPA SISWA KELAS VIII - Malinda Pramandari (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
This research aims to determine the effect of Science achievement learning of 8th-grade student of the secondary school of Pembangunan Karangmojo in academic year 2014/2015 by Snowball Throwing model and expository learning models. The experiment was conducted in SMP Pembangunan Karangmojo. This research is a Quasi-Experiment with the entire population of the 8th-grade students are 52 students. Data collection techniques using the technical documentation and multiple choices test. Test requirements include the analysis of distribution normality test, homogeneity test variants and data analysis techniques using t-test. Descriptive research results show that the trend of achievement learning that learning science using cooperative learning model Snowball Throwing and expository learning models are included category high and medium. The average score of the experimental group higher grade. Thus there is the effect of cooperative learning model Snowball Throwing on achievement learning of students of class VIII SMP IPA Pembangunan Karangmojo.